Implementasi Pembelajaran Berbasis Pengalaman dalam Membina Kemandirian dan Kepemimpinan Siswa (Proses Pengembangan Karakter dalam Konteks Pendidikan Pancasila dan Kewarganegaraaan) di SMP Adhyaksa Medan - Laia, Agustinus; Simanjuntak, Hotmaida; Pasaribu, Kondios M.D.; Pardede, Lukman; Siahaan, Monalisa Martha (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to find out if the implementation of experiential learning can foster student independence and leadership in the context of Pancasila and Citizenship Education at Adhyaksa Junior High School Medan. This type of research is qualitative descriptive, the data collection method in this study uses interviews, observations, and documentation. The data analysis techniques used are data reduction, data presentation, and conclusion drawn. The results of the study show that the implementation of experiential learning at SMP Adhyaksa Medan is carried out by integrating practical activities that are relevant to students' daily lives into the PPKn curriculum. Challenges in the implementation of experiential learning in PPKn subjects at SMP Adhyaksa Medan include limited resources, such as inadequate facilities and teaching materials. Group project efforts, simulations, and reflective discussions help students develop self-reliance and leadership skills by providing them with opportunities to be directly involved, take responsibility, and lead in a variety of contexts relevant to civic education